SUPERVISI KOLABORATIF DI PESANTREN: DARI HIERARKI KETAT MENUJU KETERBUKAAN DALAM KOMUNIKASI PENDIDIKAN - Mubarok, Ikhsan; Mursidah, Liqo’; Rofiq, Ainur (As-Sulthan Journal of Education, 2024)
The study entitled Collaborative Supervision in Islamic Boarding Schools: From Strict Hierarchy to Openness in Educational Communication explores the shift in supervision patterns in the Darul Qur'an Islamic Boarding School, North Kundur, from a fairly strict and closed hierarchical system to a more open collaborative approach in educational communication. The purpose of this study is to identify and analyze collaborative supervision models that can be applied in the Darul Qur'an Islamic Boarding School as an effort to increase the effectiveness of educational communication between the leaders of the Islamic boarding school and teachers/ustadz. This study uses a qualitative method by seeking sources from in-depth interviews and observations at the Darul Qur'an Islamic Boarding School, North Kundur to analyze the impact of collaborative supervision on the effectiveness of learning and relations between leaders and teachers/ustadz. The results of the study indicate that the implementation of collaborative supervision increases active participation and strengthens the relationship between the leaders of the Islamic boarding school and teachers/ustadz, as well as facilitating a more open exchange of ideas or opinions. The conclusion of this study is to emphasize the importance of renewal in the pattern of supervision of Islamic boarding schools with the aim of supporting a more inclusive, adaptive, and responsive learning environment to the needs of contemporary education.